Negotiating agricultural trade: Options for moving forward - Glauber, Joseph W.; Parent, Marie (International Food Policy Research Institute, 2019)
Open trade is increasingly important as countries prepare to face the coming challenges in food demand and production. The rules-based system established under the World Trade Organization (WTO) has facilitated the growth of agricultural trade, creating global welfare gains. But today negotiated settlements on tougher issues, such as domestic support, have become more difficult to obtain. The authors offer a set of seven options for modest reforms that could build confidence for moving the agricultural trade agenda forward in these challenging times.